Report on the Pacific Roundtables : Actions to Address Correspondent Banking and Remittances Pressure - Stuart, Alison; Alwazir, Jihad; Liu, Yan.; Roger, Scott (Washington, D.C. : International Monetary Fund, 2019)
The paper looks at feasible concrete action that can be taken by correspondent and respondent banks, money transfer operators, the Pacific authorities, the Australian and New Zealand authorities, and international organizations.
Off-Campus Access: No User ID or Password Required
On-Campus Access: No User ID or Password Required
Mode of access: Internet